Pengaruh Pengembangan Sumber Daya Manusia (SDM) Terhadap Kinerja Pegawai Pada Dinas Perdagangan Dan Perindustrian Kabupaten Gowa - Achmad Putra; Ahmad Ac; Muchriady Muchran (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to determine the influence of human resource development on employee performance at the Gowa Regency Trade and Industry Office. The type of research used in this study is quantitative using the SPSS 27 program data analysis method. The sample in this study is 34 people who are employees of the Gowa Regency Trade and Industry Office. The data analysis used was descriptive data analysis, research instrument analysis, classical assumption analysis, simple linear regression analysis and hypothesis testing.The results of this study show that based on the results of data analysis and t-test results obtained that the human resource development variable does not have a significant effect on employee performance at the Gowa Regency Trade and Industry Office, H0 is accepted and H1 is rejected. This is evidenced by the t-value of 1.910 > t-table 1.692, as well as the significance value of 0.065 > 0.05.